AYURVEDIC APPROCH IN THE MANAGEMENT OF AMLAPITTA WITH THE HELP OF PATHYAPATHYA - Jain, Pranjal Sanjay; Katariya, Punam Subhashlalji (International Journal of Research -GRANTHAALAYAH, 2021)
In present scenario due to modern lifestyle and food habits most of the population are suffering from a common disease called as Amlapitta or gastritis. Ayurveda is a treasure of Knowledge. Ayurvedic science helps for removing root cause of diseases with the help of various Shodhan, Shaman treatment along with Pathyapathya. After treatment of diseases if proper Pathya not followed then recurrence of diseases occurs. In Ayurveda medicines as well as Pathya has equally important. For each diseases different Pathya described in Samhitas. In present we will discuss about importance of Pathya and Apathya in Amlapitta disease. Amlapitta is one of the Annavaha Strotas disease causes due to not following proper Pathya. It’s characterized by qualitatively and quantitatively increased Amla Guna of Pitta. The cardinal classical clinical features of Amlapitta are Avipaka (indigestion), Klama (tiredness), Utklesha (nausea), Tikta Amlaudagar (sour and bitter belching), Hrutakantha Daha (heat and throat burn) and Aruchi (anorexia). In Pathya Kalpana not only Hetus but proper follow of Dincharya and Rutucharya are important. Here attempted has to be made for various Pathya and Apathya are applicable for Amlapitta.